Projected Impacts of United States Trade Policies Under a Potential Second Trump Administration on Malaysia - Reindra, Nanda; Nurviani, Nanny; Armaya, Shendy Devendra; Shahrullah, Rina Shahriyani (Hang Tuah Law Journal, 2026)
The international trade policies of United States President Donald Trump, particularly the imposition of high import tariffs on Malaysian products, have significantly affected Malaysia’s economy and trade relations. Tariffs of up to 24–25% starting in August 2025 have increased trade tensions and pressured key export sectors, especially maritime and manufacturing industries. This study aims to analyze the impact of these tariff policies on Malaysia’s export performance to the United States. It also examines Malaysia’s response strategies, including diplomacy and negotiations through bilateral and ASEAN forums, to reduce negative effects and maintain economic stability. In addition, the policies have raised risks of inflation and supply chain disruptions due to Malaysia’s reliance on raw materials and export markets. These challenges highlight the need for domestic policy adjustments and stronger regional cooperation. The study also discusses legal implications, including challenges to WTO free trade principles. Overall, the findings emphasize the importance of flexible national policies and regional solidarity to sustain Malaysia’s competitiveness in a changing global trade environment.